MULTIFACTOR EXPERIMENT, EXPERIMENTAL RESULTS AND DEVELOPMENT OF REGRESSION EQUATIONS IN WELDING AND APPLICATION OF COATINGS ON EXCAVATOR BUCKET TEETH - Zulfikorov Dostonbek Rustamjon ogly (Bright Mind Publishing, 2025)
The results of testing some types of alloys revealed the potential of using metastable austenitic wear-resistant alloys to strengthen the working parts of excavator bucket teeth. However, alloys 55X7 G7T and 100X6 Alloys G6S3FAP, the alloys selected as prototypes for optimization have shortcomings that determine the need for further work on optimizing the composition of the coating material. Alloy 55X7 G7T has unsatisfactory strength characteristics. Active phase-bound kinetics leads to an increase in resistance to microscratching , but does not contribute to the preservation of the plastic resource under additional impact-abrasive effects. Optimization should be carried out in the direction of obtaining stretched kinetics with the preservation of residual austenite due to the carbon content in the solid solution. To improve wear resistance without reducing the strength properties, an increase in the amount of the carbide phase can be achieved, as indicated above, by replacing chromium carbides with finely dispersed special VC carbides in a vanadium alloy. An additional reserve is the introduction of calcium silicate into the surfacing process for grinding and orienting the dendritic structure and increasing the number of aligned crystals. A positive example of the use of calcium silicon as a modifier in coatings for flux-cored wire welding can be seen in [ 1].
Keywords: Excavator, bucket, tooth, protective element, efficiency, trouble-free operation, reliability, rock, abrasive wear, hard coating, coating, weld seam.